Colombia : Request for an Arrangement under the Flexible Credit Line and Cancellation of the Current Arrangement - Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2022)
Colombia's very strong policy frameworks and comprehensive policy response to the pandemic have supported the economy's resilience. With stronger-than-expected growth last year, fiscal deficits and public debt are declining faster than anticipated, and the fiscal framework has been reactivated with a new fiscal rule and debt anchor. Further monetary policy tightening should drive inflation towards the central bank's inflation target by mid-2024. Successful credit support measures in the financial sector are being phased out and, as discussed in the recent FSAP, financial sector supervision and regulation have been enhanced since the previous staff assessment. Overall, the authorities remain committed to maintaining their very strong policy framework as seen by steps taken to normalize policies from a crisis footing in the pandemic. Political assurances on policy continuity from the leading candidates provide a necessary safeguard for the proposed arrangement.